(untitled) (Journal of Computational Mathematics, 2021)
In this paper, we provide simple and explicit formulas for computing Riemannian curvatures, mean curvature vectors, principal curvatures and principal directions for a 2-dimensional Riemannian manifold embedded in R^k with k≥3.